Misophonia: current perspectives - Cavanna, Andrea E (Neuropsychiatr Dis Treat, 2015)
Misophonia is characterized by a negative reaction to a sound with a specific pattern and meaning to a given individual. In this paper, we review the clinical features of this relatively common yet underinvestigated condition, with focus on co-occurring neurodevelopmental disorders. Currently available data on the putative pathophysiology of the condition can inform our understanding and guide the diagnostic process and treatment approach. Tinnitus retraining therapy and cognitive behavior therapy have been proposed as the most effective treatment strategies for reducing symptoms; however, current treatment algorithms should be validated in large population studies. At the present stage, competing paradigms see misophonia as a physiological state potentially inducible in any subject, an idiopathic condition (which can present with comorbid psychiatric disorders), or a symptomatic manifestation of an underlying psychiatric disorder. Agreement on the use of standardized diagnostic criteria would be an important step forward in terms of both clinical practice and scientific inquiry. Areas for future research include phenomenology, epidemiology, modulating factors, neurophysiological underpinnings, and treatment trials.